Project Success and Knowledge Management (KM) practices in Malaysian Institution of Higher Learning (IHL) - Md. , Nasiruzzaman; A. Qudaih, Hani; Ahmad Dahlan, Abdul Rahman (International Foundation for Research and Development (IFDR), 2013)
The purpose of this research is to identify the relationship of project success and knowledge management practices in Malaysian Institutions of Higher Learning (IHL). As it is known the fact that the institutions of higher learning are dedicated in knowledge management business due to their nature of jobs like knowledge creation, learning and deployment. The findings suggest that there is a strong relationship between project success and the knowledge management practices implementation process, which is based on, procure proper knowledge and practices, willing and dedicated leadership,strong ICT infrastructure and value based organizational culture where successful knowledge transfer play as the mediator role. This research provides a clear view for researchers and enthusiasts regarding success factors that may influence project success in implementing KM practices in IHL and other homogenous organizations. This research is a pouring key ingredient for researchers to re-think about implementing KM Strategies for the Institutions of Higher Learning.